War Rooms: Interiors Under Siege in Beirut and Baghdad - Audisho, Endriana (Idea Journal, 2025)
Few forces disrupt the stability of architectural planning and the intended use of interior spaces more profoundly than conflict. In cities marked by war, interiors become sites of both resistance and adaptation, where the prescribed ideals of design are reshaped by the exigencies of survival, displacement, and the reorganisation of social and spatial orders. Historically, certain architectural typologies, particularly hotels, have had their interiors reconfigured in unplanned ways, repurposed for strategic, functional, and humanitarian roles that position them at the centre of conflict. This essay examines the interiors of two such hotels — the Holiday Inn in Beirut and the Al-Rashid Hotel in Baghdad — to explore how their spaces were reconfigured during conflict in response to distinct geopolitical and military needs. During the Lebanese Civil War’s ‘Battle of the Hotels’ (1975–1976), the Holiday Inn, situated along what was rapidly emerging as Beirut’s Green Line, was transformed into a fortified military stronghold. Its upper floors and rooftop were converted into sniper positions, turning the interior into a key site of resistance. In contrast, during the Gulf War in 1991, the Al-Rashid Hotel became a media hub for international correspondents. Journalists from Cable News Network navigated its interior features, such as strip windows and expansive rooms, to provide 24-hour real-time coverage of the war. The following analysis employs a methodology that draws on journalistic accounts from both case studies. These include textual, visual, and video media, which are synthesised to bring together heterogeneous sources and spatialise the transformations of space under siege. By examining these unplanned conditions, the essay argues that architecture responds to the shifting moral, social, and spatial contexts of conflict. Methods of composite analytic drawing are used to visualise how space is reconfigured under siege, and reframes hotel interiors as contingent infrastructures that unsettle assumptions about planning and design. These case studies highlight how architecture is reshaped in times of crisis, revealing its entanglement with the evolving realities of conflict.